The Effect Of Big Data Technology On Financial Performance Ini Banking Companies With Cost Reduction On The Indonesia Stock Exchange - Amelia, Dela; Windiarti , Sofia (Jurnal Ekonomi, 2024)
Accroding to data from the financial service authority (OJK) the banking sector demostrated resilience to risk and economic crises by consistently recording profit with positive value in CAR and ROA. Owever, in recent years there has been a signification decline, accompanied by an increase in the operational expenses to operational income ratio (BOPO) wich requires future attention. Since banks play a crucial role as financial intermediaries their quality and soundness must be maintained to meet standards and prevent any negative impac on national economic stability. This research aims to examine the influence of big data technology on financial performance by consider cost reduction. The population of this study is a banking company listed on the Indonesia Stock Exchange in 2018-2023. By using purposive sampling in sample selection obtained 42 research samples over 6 firm-years. This research uses multiple regression analysis to test the hypothesis. The findings of this research reveal that big data technology does not have a significant effect on financial performance. Cost Reduction has a positive and significant influence on financial performance, indicating that cost reduction efforts contribute greatly to improving the company's financial performance. Big data technology simultaneously influences financial performance through cost reduction